LIFE SIMULATION OF MICROSCOPIC SHORT CRACK NUCLEATION AND EARLY PROPAGATION OF WELD TOE - CHENG LiFu; WEI GuoQian; HU Ke; JIANG YongSheng (Jixie qiangdu)
For cross welded joints, the behavior of microscopic short crack nucleation and early propagation of the weld toe was studied. Using the Voronoi method, a representative element（RE） with a side length of 150μm at the weld toe was established. Based on the distribution characteristics of the fatigue indicator parameter（FIP）, the fatigue life between FIP and microscopic short crack was constructed.The nucleation of microscopic short crack and their early propagation life were calculated. The results show that the calculated life of weld toe microscopic short crack nucleation and its early propagation is more consistent with the test life data, indicating the applicability of this calculation method; the calculated life of microscopic short crack nucleation and its early expansion accounted for a larger ratio of the overall fatigue life, so it has a non-negligible impact; affected by the microstructure of the grains, the propagation path of the early cracks presents an obvious tortuous shape.